The proposed Council Directive on implementing the principle of equal treatment between persons irrespective of religion or belief, disability, age or sexual orientation: difficulties faced by sexual orientation - Ramiņa, Jolanta (Riga Graduate School of Law, 2020)
The author examines legislation designed to counteract discrimination related to sexual orientation in this paper. The work is based on the analysis of two controversial trends in modern society: decriminalization of LGBT communities and legalization of same-sex relationships, as well as ongoing homophobic practices in some countries that focus on so-called traditional values. The paper considers the legal regulation of actual marriage unions (cohabitation), registered partnerships and same-sex marriages by the norms of current European legislation. A study of the institution of marriage and registered partnerships led to the conclusion that the registered partnership was created for legal registration of same-sex groups, but heterosexual couples use such registration these days as well. The author concluded that today there is an irreversible process of recognition of same-sex couples, which is rapidly spreading throughout the world. Thus, the development of international, regional and, as a consequence, national law is aimed at the full equality and realization of the rights and freedoms of all citizens regardless of their sexual orientation, despite the existence of countries in which same-sex relationships are still stigmatized.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Family law